Bank syariah di Indonesia : analisis kebijakan pemerintah Indonesia terhadap perbankan syariah - Kara, Muslimin H., 1971- (Yogyakarta : UII Press, 2005)
Study on government policy in Islamic banking in Indonesia.
Originally presented as the author's thesis (S3--UIN Syarif Hidayatullah, 2003) under title: Kebijakan pemerintah Indonesia tentang perbankan Islam.
Includes bibliographical references
Keywords: Banks and banking -- Indonesia -- Religious aspects -- Islam; Banks and banking -- Islamic countries